Community‐supported models of care for people on HIV treatment in sub‐Saharan Africa. Issue 8 (28th May 2014) - Bemelmans, Marielle; Baert, Saar; Goemaere, Eric; Wilkinson, Lynne; Vandendyck, Martin; van Cutsem, Gilles; Silva, Carlota; Perry, Sharon; Szumilin, Elisabeth; Gerstenhaber, Rodd; Kalenga, Lucien; Biot, Marc; et al.
Abstract Objectives Further scale‐up of antiretroviral therapy (ART) to those in need while supporting the growing patient cohort on ART requires continuous adaptation of healthcare delivery models. We describe several approaches to manage stable patients on ART developed by Médecins Sans Frontières together with Ministries of Health in four countries in sub‐Saharan Africa. Methods Using routine programme data, four approaches to simplify ART delivery for stable patients on ART were assessed from a patient and health system perspective: appointment spacing for clinical and drug refill visits in Malawi, peer educator‐led ART refill groups in South Africa, community ART distribution points in DRC and patient‐led community ART groups in Mozambique. Results All four approaches lightened the burden for both patients (reduced travel and lost income) and health system (reduced clinic attendance). Retention in care is high: 94% at 36 months in Malawi, 89% at 12 months in DRC, 97% at 40 months in South Africa and 92% at 48 months in Mozambique. Where evaluable, service provider costs are reported to be lower. Conclusion Separating ART delivery from clinical assessments was found to benefit patients and programmes in a range of settings. The success of community ART models depends on sufficient and reliable support and resources, including a flexible and reliable drug supply, access to quality clinical management, a reliable monitoring system and a supported lay workers cadre. Such models require ongoing evaluation and further adaptation to be able to reach out to more patients, including specific groups who may be challenged to meet the demands of frequent clinic visits and the integrated delivery of other essential chronic disease interventions.